The Role of Educational Technology (EdTech) in Improving the Quality of Science Learning: A Narrative Review - Gisna Haerani; Dini Sudianti (Indonesian Publication Center, 2025)
The development of digital technology has brought significant transformation in education, particularly in science learning, which requires visualization and direct experiences to understand abstract concepts. This study aims to describe the role of digital technology in improving the quality of science learning through an analysis of various studies related to interactive media, digital simulations, AR/VR, virtual laboratories, and digital literacy. This study employed a narrative review approach by examining relevant scientific articles obtained from Google Scholar. The articles were analyzed based on the type of technology used, the purpose of implementation, and their impact on science learning outcomes. The results indicate that digital technologies such as PhET simulations, interactive multimedia, gamification applications, AR/VR, and virtual laboratories consistently improve conceptual understanding, learning motivation, student engagement, and scientific literacy. Digital technology also helps overcome the limitations of conventional learning through the visualization of abstract concepts and more immersive learning experiences. However, its implementation still faces challenges, including limited device availability, internet access, and teacher readiness. Overall, digital technology has great potential to strengthen the effectiveness of science learning when supported by teacher competence and adequate infrastructure.